Design of software to calculate the carbon and water footprint during coffee production (2018)
Introduction: The article derives from the research “Software design for carbon and water footprint calculation in coffee production” conducted at the Universidad Cooperativa de Colombia, Neiva, in the period 2016-2017.Aim: To design software for calculating carbon and water footprints in coffee production.Methods: The research process is both qualitative and quantitative, acknowledging opinions, contexts and experiences of coffee farmers in the municipalities of Acevedo, San Agustín, San José de Isnos and Pitalito.Results: The design of a web application to calculate carbon footprints and water footprints in coffee growing, integrating technologies under a free software license that show performance efficiency and effectiveness.Conclusion: The xp methodology ensures flexible development in software design, which will allow carbon and water footprint calculation adaptable to changes and requirements in a short time and at a low cost.Originality: So far there is no evidence in the literature of a design for carbon and water footprint calculation in coffee production in southern Huila.Limitations: This project used a methodology that may be applied to various crops; however, footprint calculations are specific to these areas given the environmental variables